A Study of Explicit and Implicit Means of Connection in Monologic Supraphrasal Reported Speech - Mkhitaryan, Yelena; Tamoyan, Nare (Armenian Folia Anglistika, 2013)
The article, which views the monologic reported speech as a unique supraphrasal unity, aims to investigate the explicit and implicit means of connection that ensure the structural and semantic, as well as communication wholeness of the reported speech. The explicit means connecting the members of the monologic supraphrasal reported speech are anaphoric and cataphoric conversion, interjections and connective words, syntactic parallels, etc. while the implicit connection is expressed by semantic-logical relations (causal, adversative, time) existing between the other constituents of the monologic supraphrasal reported speech, rather than by linguistic means of connection.